Novel HfxTa1−xC solid solution nanowire toughened HfC coating: An effective strategy for synchronous enhanced mechanical and anti-ablation performance - Hui Chen; Yulei Zhang; Yanqin Fu; Wenhan Gai; Junhao Zhao; Haohui Zhang (Journal of Advanced Ceramics, 2024)
Ultra-high-temperature ceramic nanowires have shown increasing potential for use as thermal structural components. Herein, novel single-crystal Hf0.5Ta0.5C solid solution nanowires were synthesized and incorporated with a HfC coating to construct a robust structure with Hf0.5Ta0.5C solid solution nanowires uniformly distributed and interconnected within the coating. The novel Hf0.5Ta0.5C solid solution nanowires could effectively hinder crack propagation through crack tip pinning and crack deflection. This mechanism substantially enhanced the elastic modulus and fracture toughness of the HfC coating by 53.29% and 59.67%, respectively. The toughened HfC coating displayed superior fracture toughness and good interfacial binding strength with the substrate to resist severe oxidation and scouring. Additionally, the high thermal conductivity of the toughened HfC coating promoted heat transmission. Thus, in comparison to the pure HfC coating, the toughened HfC coating displayed smaller mass and linear ablation rates of −0.35 mg·s−1 and −0.46 μm·s−1, which decreased by 39.66% and 36.98%, respectively. Our work not only simultaneously enhances the mechanical properties and ablation resistance of HfC-coated carbon/carbon (C/C) composites but also provides novel prospects for advanced ultrahigh-temperature ceramic nanowires under extreme conditions.